Performance on soil utilization model as interlock block wall material - Muhammad Zakaria Umar (Universitas Mercu Buana, 2022)
Soil characteristics around Kendari City are included in the clay soil category. So far, clay has not been used optimally. Clay is only used as a pile material in buildings. The land around the city of Kendari can be made of brick interlock material. This research is important to be carried out to utilize the surrounding land as building wall material to obtain an economical and effective wall material. This study aimed to test the Land Use model's compressive strength and water absorption performance as an interlock block material in Kendari City. In this study, three treatments were made. Each treatment made 10 test specimens. Test specimens are made with a size of 25 cm x 12.5 cm x 10 cm. The research steps are preparing work tools, preparation of work materials, dry stirring process, moist stirring process, printing, drying, watering, testing, and data analysis. Data collection techniques are carried out in the laboratory. Testing includes compressive strength and water absorption. Based on the results of tests in the laboratory, interlocking brick from the ground has low compressive strength and water absorption. Interlock block can be used as a wall under the following conditions: first, the interlock brick material using clay is the same as the clay used by red brick material; second, interlock brick material from the soil is added with sand material.